2022
DOI: 10.1111/1541-4337.12885
|View full text |Cite
|
Sign up to set email alerts
|

Cold plasma for the disinfection of industrial food‐contact surfaces: An overview of current status and opportunities

Abstract: Food safety is the primary goal for food and drink manufacturers. Cleaning and disinfection practices applied to the processing environment are vital to maintain this safety; yet, current approaches can incur costly downtime and the potential for microorganisms to grow and establish, if not effectively removed. For that reason, manufacturers are seeking nonthermal, online, and continuous disinfection processes to control the microbial levels within the processing environment. One such emerging technique, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 256 publications
(455 reference statements)
0
15
0
Order By: Relevance
“…Another great advantage and potential for industrial application of CP pretreatment for dry products is the reduction of safety risks. More and more studies have shown that CP can degrade pesticides (Gavahian & Khaneghah, 2020), biotoxins (Yue, Jun‐Hu, & Da‐Wen, 2021), and kill pathogenic and spoilage bacteria in food (Katsigiannis, Bayliss, & Walsh, 2022), thereby enhancing the safety and storage stability of dried products. It will facilitate the choice of CP pretreatment in the drying industry.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another great advantage and potential for industrial application of CP pretreatment for dry products is the reduction of safety risks. More and more studies have shown that CP can degrade pesticides (Gavahian & Khaneghah, 2020), biotoxins (Yue, Jun‐Hu, & Da‐Wen, 2021), and kill pathogenic and spoilage bacteria in food (Katsigiannis, Bayliss, & Walsh, 2022), thereby enhancing the safety and storage stability of dried products. It will facilitate the choice of CP pretreatment in the drying industry.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%
“…As a gradually emerging treatment technology, cold plasma (CP) is widely used in antibacterial (Zhu et al., 2020), food composition and film modification (Bahrami et al., 2020; K. Zhang et al., 2019), food contaminant treatment(W. Yue et al., 2021), disinfection (Katsigiannis et al., 2022), and so on. Plasma is considered the fourth state of matter besides liquid, solid, and gas.…”
Section: Introductionmentioning
confidence: 99%
“…In our study reveals that DBD plasma exposure duration 5–60 min against L. monocytogenes on smoked salmon by 0.17–1.25 log CFU/g (Table 1). It has been reported after DBD plasma treatment Salmonella enterica serovar Heidelberg on lettuce and chicken breast were reduced by ∼4.5 and 3.7 log 10 CFUs, respectively (Aboubakr et al, 2020; Katsigiannis, Bayliss, & Walsh, 2022). The counts of total aerobic bacteria, L. monocytogenes , E. coli , and Salmonella Typhimurium were reduced by 3.36, 2.14, 2.73, and 2.71 Log CFU/g, respectively, after a 10 min plasma treatment (Lee, Yong et al, 2016; Lee, Park, & Ha, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, solid end-yields might be created primarily by low-temperature thermal degradation pyrolysis. As a result, coke, carbon black and char will be gathered [23] , [24] .…”
Section: Methodsmentioning
confidence: 99%